The Nobility of Toulouse in the Eighteenth Century A Social and Economic Study - Forster, Robert (Johns Hopkins University Press, 1960)
Originally published in 1960. This is a regional study of the nobility of Toulouse in the eighteenth century. The complex notion of class and the peculiarities of each region in France during the Ancien Régime make it difficult for historians to render a general portrait of the provincial French aristocracy. This study describes the economic interests and investments of noblemen in Toulouse. Some of their activities follow the classic pattern of "seigniorial reaction" and thus illustrate ideas posed by Marc Bloch. Others suggest that the Toulousian gentlemen were conscientious landlords. The Toulousian noble was essentially a gentilhomme campagnard, a country gentleman, in regard to his source of revenue, his outlook, and his mode of living. This book should make clear the full meaning of this expression.